Rekonstruiranje zgodovinskih jezikovnih situacij - Ahačič, Kozma (Jezik in slovstvo, 2006)
The article presents some methods, problems and rules of reconstructing historical linguistic situations within historical socio-linguistics. It focuses on determining language use according to social status (farmers, urbanpopulation, nobility), looking also at the more complex linguistic repertoires of educated individuals living in a particular period. The articlecalls attention to the influence of the educational process on a linguistic situation, the role played by the use of different languages withinthe same text or book in observing the linguistic situation, the differences between the text producers and addressees of the literary texts ofa period, the need for specific treatment of normative works with respect totheir influence on the historical linguistic situation, and the reflection of the linguistic situation in the discourse of the time (especially terminology), while pointing out the problematic use of the labels for language, dialect and speech within a given period.
Keywords: Slovene; slovenščina; sociolingvisitka; zgodovina jezika